KEINGINAN BERWIRAUSAHA MAHASISWA PADA PENGARUH KOMPETENSI KEWIRAUSAHAAN, MOTIVASI BERWIRAUSAHA DAN KREATIVITAS BERWIRAUSAHA - Nurhasanah Nurhasanah; Didin Hikmah Perkasa; Magito Magito; Fathihani Fathihani; Muhammad Al Faruq Abdullah; Islamiah Kamil (Jurnal Manajemen dan Bisnis, 2023)
The main objective of this study is to determine the entrepreneurial desire of students on the influence of entrepreneurial competence, entrepreneurial motivation and entrepreneurial creativity on students at the University of West Jakarta. The research design uses a quantitative descriptive approach. Data in the study were obtained from 175 respondents who are university students in West Jakarta using a questionnaire as a data collection tool with the survey method. Data analysis in this study using the SEM PLS test tool was carried out testing discriminat validity, convergent validity, composite reliability, outer model, inner model and hypothesis testing. The first stage in this study is to test the validity of the questions of each variable along with their reliability. The second stage tests the influence of each variable. The results showed that there is an influence of entrepreneurial competence, entrepreneurial motivation and entrepreneurial creativity on student entrepreneurial desire.